2018
DOI: 10.3906/biy-1802-11
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anticancer effect of tricyclic antidepressant nortriptyline on multiple myeloma

Abstract: Drug repurposing has been proved to be an effective strategy to meet the urgent need for novel anticancer agents for multiple myeloma (MM) treatment. In this work, we aimed to investigate the anticancer effect and mechanism of tricyclic antidepressant nortriptyline (NTP) on the U266 MM cell line. The in vitro inhibitory effect of NTP at various doses and time points was studied. The combination potential of cisplatin-NTP was also investigated. Cell cycle analysis and three flow cytometric apoptosis assays were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Thus, it is the first evidence of the positive effects of repair and activation of adaptation mechanisms to stress conditions. Others also indicate a cycle arrest in the G2/M phase or S, suggesting that antidepressants can exhibit cytotoxic properties and induce apoptotic cell death possibly via a mitochondrial independent pathway [ 21 , 22 ]. In turn, cell cycle arrest in the G0-G1 phase may be associated with the inhibition of cyclin D2 activity in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is the first evidence of the positive effects of repair and activation of adaptation mechanisms to stress conditions. Others also indicate a cycle arrest in the G2/M phase or S, suggesting that antidepressants can exhibit cytotoxic properties and induce apoptotic cell death possibly via a mitochondrial independent pathway [ 21 , 22 ]. In turn, cell cycle arrest in the G0-G1 phase may be associated with the inhibition of cyclin D2 activity in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding tricyclic antidepressants, nortriptyline has shown anticancer effects, particularly in PC, because it inhibits cell proliferation and induces apoptosis due to increased intracellular calcium in PC cells and induces cytotoxicity through cell cycle interruption by inhibition of CDK1 and by inhibiting Rb expression, affecting the Rb/E2F complex and, consequently, inhibiting the expression of E2F target genes, since Rb phosphorylation must occur for E2F to be separated from the Rb/E2F complex and activate the expression of genes required for the S-phase transition [ 40 , 41 , 42 ].…”
Section: Pharmacotherapeutic Groups With Potential Efficacy In Pc Tre...mentioning
confidence: 99%
“…Drug repurposing has been proved to be an effective strategy to meet the urgent need for novel anticancer agents for multiple myeloma (MM) treatment. The TCA nortriptyline has shown greater inhibitory and apoptotic effects in U266 MM cells than cisplatin; however, the cisplatin-nortriptyline combination also indicated strong antagonism [92]. Ten years ago, in vitro and in silico studies demonstrated that amitriptyline showed anti-myeloma ac-tivity by inducing cell apoptosis through the inhibition of histone deacetylases [90].…”
Section: Multiple Myelomamentioning
confidence: 99%